Determinant Of Sharia Stock Returns And The Impact Of The Pandemic As Moderation Variables (Case Study of Jakarta Islamic Index (JII) for the 2017-2021 Period) - Muhammad Ridha Irsyadillah; Atika Rukminastiti Masrifah (Jurnal Akuntansi Indonesia, 2023)
ABSTRACT The aim of this research is to carry out further tests on the variables that influence Sharia Stock Returns on the Jakarta Islamic Index (JII) by considering the Covid-19 pandemic as a moderating variable. The research population is companies registered on the Jakarta Islamic Index (JII) for 2017 - 2021. The data was analyzed using a purposive sampling technique, 95 data were obtained. Data were analyzed using the E-Views analysis technique. The results of this research indicate that the variables EPS, DER, ROA, CR have no significant effect on Islamic stock returns, but the pandemic variable can affect Islamic stock returns. Meanwhile, the moderating impact of the pandemic on the relationship between EPS, DER, ROA, CR variables on Sariah's stock returns is not proven. These results provide empirical evidence that the pandemic has greatly worsened Islamic stock prices in the Journal of Islamic Index (JII).Keywords: Pandemic Covid 19, Stock Return, Profitability, Sovabilty, Likuidity ABSTRAKTujuan Riset ini adalah ingin melakukan pengujian lebih lanjut terhadap variabel-variabel yang mempengaruhi Return Saham Syariah di Jakarta Islamic Index (JII) dengan mempertimbangkan pandemi Covid-19 sebagai variabel moderasi. Populasi riset ini adalah perusahaan yang terdaftar di Jakarta Islamic Index (JII) tahun 2017 - 2021. Data dinalisis menggunakan Teknik purposive sampling diperoleh data sebanyak 95 data. Data dianalisis menggunakan teknik analisis E-Views. Hasil riset ini menunjukkan bahwa variabel EPS, DER, ROA, CR tidak berpengaruh signifikan terhadap Return Saham Syariah namun variabel pandemic mampu mempengaruhi return saham syariah. Sedangkan dampak moderasi pandemic terhadap hubungan variabel EPS, DER, ROA, CR terhadap return saham Sariah tidak terbukti. Hasil ini memberikan bukti empiris bahwa pandemic sangat memperburuk harga saham syariah di Jurnal Islamic Index (JII).Keywords: Pandemic Covid 19, Return Saham, Profitabilitas, Sovabiltas, Likuiditas